2021
DOI: 10.1021/acs.jmedchem.1c00477
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Peptides That Antagonize the Angiotensin-Converting Enzyme-2 (ACE-2) Interaction with SARS-CoV-2 Receptor Binding Spike Protein

Abstract: The SARS-CoV-2 viral spike protein S receptor-binding domain (S-RBD) binds ACE2 on host cells to initiate molecular events, resulting in intracellular release of the viral genome. Therefore, antagonists of this interaction could allow a modality for therapeutic intervention. Peptides can inhibit the S-RBD:ACE2 interaction by interacting with the protein–protein interface. In this study, protein contact atlas data and molecular dynamics simulations were used to locate interaction hotspots on the secondary struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 77 publications
(166 reference statements)
0
32
0
Order By: Relevance
“…Furthermore, antibodies are very large molecules, which may hamper tissue penetration, as well as access to sterically shielded epitopes. Therefore, current research is also focused on developing alternative, smaller molecules capable of interfering with the interaction of the SARS-CoV-2 spike protein with cellular ACE2 [ 12 , 13 , 14 , 15 ]. Over the past two years, a range of studies have reported the computational design of smaller proteins or peptides, either based on the structure of the two N-terminal α-helices of ACE2, through which it contacts the receptor binding domain (RBD) of the SARS-CoV-2 spike protein [ 16 , 17 , 18 , 19 ], or through de novo design based on the RBD structure [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, antibodies are very large molecules, which may hamper tissue penetration, as well as access to sterically shielded epitopes. Therefore, current research is also focused on developing alternative, smaller molecules capable of interfering with the interaction of the SARS-CoV-2 spike protein with cellular ACE2 [ 12 , 13 , 14 , 15 ]. Over the past two years, a range of studies have reported the computational design of smaller proteins or peptides, either based on the structure of the two N-terminal α-helices of ACE2, through which it contacts the receptor binding domain (RBD) of the SARS-CoV-2 spike protein [ 16 , 17 , 18 , 19 ], or through de novo design based on the RBD structure [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…43 This interaction is an essential route of entry for SARS-CoV-2. 44 For demonstration of the use of thiolene chemistry in DESs on an analogue of this peptide, the peptide sequence CEDLFYQ (23) was synthesised by Fmoc-SPPS, wherein the Cys residue replaces an alanine in the sequence of the human protein, and provides the thiol moiety for functionalisation of the peptide without alteration of the minimal sequence required for binding. The optimised UVinitiated conditions were applied to the peptide with excess cyclohexene, as this alkene is commercially available and had shown good yield in both UV-and O 2 -initiated TEC with Boc-Cys-OMe.…”
mentioning
confidence: 99%
“…elements of the interface. In the case of RBD/ACE2 interface, different peptides recapitulated the main H1 helix (partially or entirely) with minor conformation adjustments (Figure 3A) Likewise, in the case of the ACE2/ACE2 interface, peptides also show a helical conformation similar to the helix that mediates the interaction between ACE2 monomers (Figure 3B) Redesigned native elements, such as the main H1 helix, has been shown to inhibit the interaction between RBD and ACE2 ( [8,[25][26][27]). Besides recapitulation of native structural elements, designed peptides also presented novel conformations not observed in the native complexes.…”
Section: Structural Diversity Among Designed Peptidesmentioning
confidence: 99%
“…In the context of viral infection examples such as the FDA-approved peptide Enfurvirtide [16] and further research (reviewed in [17,18]) illustrate the use of peptides as potential agents to block PPIs. In fact, a number of recent publications has shown promising results on the use of peptides to blocks the entrance of SARS-CoV-2 virus using peptides derived from native element of the interaction humanACE2 and SARS-CoV-2 spike [19][20][21] including designed peptides targeting of the heptad repeat 1 region [22], the RBD domain [23][24][25], with validation in cell-cultures [26,27] and tissues [28]. While these approaches rely on the sequence diversification of existing native elements, ours complements these efforts by providing novel sequences (next).…”
Section: Introductionmentioning
confidence: 99%